Behaviour and design of earthquake resistant low-rise shear walls. - Mohammadi-Doostdar, Hossein. (University of Ottawa (Canada), 1994)
A combined experimental and analytical research was conducted to investigate behaviour of low-rise concrete shear walls under simulated seismic loading. The experimental part of the research program includes tests of two large-scale shear wall specimens under inelastic load reversals. The walls were 1500 mm high and 100 mm thick, and had either 2000 mm or 1500 mm lengths, producing aspect ratios of 0.75 and 1.0. The effect of aspect ratio on shear sliding and failure modes was one of the major test parameters. The results indicated that both walls were able to develop flexural yielding and failed in crushing of diagonal struts. Little or no strength decay was observed up to approximately 0.92% and 1.83% lateral drift in walls with aspect ratios of 0.75 and 1.0, respectively. Shear sliding was limited to approximately 10% of total lateral displacement, prior to the onset of strength degradation, indicating no premature failure caused by this mechanism. The deformation components indicate that flexure and shear were equally important in these walls, and formed approximately 80% of total lateral displacement. A new analysis procedure was developed as part of the analytical investigation. The procedure can be used for strength and deformation computations for low-rise shear walls with aspect ratios of 1.0 or less. It is based on equilibrium, compatibility, and material models. Potential failure planes are first identified and analyses of wall sections are carried out. One of the potential failure planes is the horizontal wall section at the base, and is critical against flexure. A standard plane section analysis is conducted at this section. The compression region determined from the plane section analysis is used to establish the second failure plane, which is inclined towards the loading corner. An inclined section analysis is conducted along this section based on experimentally observed strain variation. Diagonal compression in inclined concrete strut is checked against crushing. The strain condition computed from the inclined section analysis provide sufficient information to establish shear force-shear deformation relationship. The analysis procedure has been verified extensively against available test data. The analytical approach was simplified for use in design. A design procedure is recommended for low-rise shear walls with aspect ratios of 1.0 or less.
Keywords: Engineering, Civil.